DATA VISUALIZATION AS A TOOL FOR PUBLIC UNDERSTANDING EDUCATION - Suvita, Yalda; Anjarika, Adelina Lintang; Hutami, Nurahmi Resnanti; Mayfani, Silviedriya; Ahman, Ahman (Universitas Pendidikan Indonesia, 2025)
Data visualization is a graphical representation of information designed to facilitate understanding and decision making. The purpose of this study is to explore the importance of data visualization as an educational tool in improving public understanding of complex information. This study uses a qualitative descriptive approach with a literature study method. Secondary data collected comes from various trusted sources such as scientific journals, articles, books, and other research documents. The results of this study are that data visualization has proven to be a very effective educational tool in improving public understanding of complex information. The use of visualization techniques, such as graphs, diagrams, and animations, makes difficult information can be presented in a concise and more attractive form. The principles that must be possessed by good data visualization are simplicity, relevance, readability, and visual appeal. So, the information to be conveyed can be understood by all members of the general public.